Design optimization of sandwich panels under impact loads. Issue 9 (2nd September 2021) - Shobeiri, Vahid
Abstract : The purpose of this article is to develop numerical models for topology optimization of sandwich panels subjected to impact loads. Numerical models account for the effects of energy absorption capability and impact load resistant capacity on the development of optimal designs. A topology optimization technique based on the evolutionary structural optimization method and nonlinear dynamic finite element analysis with deflection and periodic constraints is used to generate optimal designs of sandwich panels under impact loads. To demonstrate the efficiency of the proposed method, design optimization of various sandwich panels is evaluated. A parametric study is conducted to investigate the effects of unit cells, core height, stiffener configuration and impact load intensity on the optimal designs. Up to 50% reduction in weight, 30% increase in energy absorption and 30% decrease in boundary reaction forces are achieved. Thus, the proposed approach can provide reliable manufacturing designs for sandwich panels under impact loads.